1996
DOI: 10.1159/000246272
|View full text |Cite
|
Sign up to set email alerts
|

Does Hormonal Skin Aging Exist? A Study of the Influence of Different Hormone Therapy Regimens on the Skin of Postmenopausal Women Using Non-Invasive Measurement Techniques

Abstract: Background and Design: The skin properties of 98 postmenopausal women with hormone replacement therapy (oestradiol gel or patches) or without hormone replacement therapy were studied using non-invasive techniques: skin thickness with skin echography, skin hydration with a dryness score and measurement of capacitance, skin surface lipids with a Sebumeter® and microtopography with image analysis of cutaneous replicas. Results: In this open study we demonstrated an increase in skin thickness and sebum in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(86 citation statements)
references
References 0 publications
4
74
1
7
Order By: Relevance
“…Hormone replacement therapy has been correlated with enhancement of collagen production, increase in skin thickness, surface lipids, hydration, vascularisation and increase of the hair follicle life cycle (Brincat, 2000;Callens et al, 1996;Fuchs et al, 2003;Patriarca et al, 2007;Sator et al, 2007;Sator et al, 2001) leading to an improvement of skin tone and appearance. Hormone replacement may only improve the skin quality in female patients treated during the first 24 months after menopause (Phillips et al, 2008) (Table I).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Hormone replacement therapy has been correlated with enhancement of collagen production, increase in skin thickness, surface lipids, hydration, vascularisation and increase of the hair follicle life cycle (Brincat, 2000;Callens et al, 1996;Fuchs et al, 2003;Patriarca et al, 2007;Sator et al, 2007;Sator et al, 2001) leading to an improvement of skin tone and appearance. Hormone replacement may only improve the skin quality in female patients treated during the first 24 months after menopause (Phillips et al, 2008) (Table I).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…En relación con el envejecimiento microscópi-co, Callens et al 20 trataron a 98 mujeres con estradiol en gel o parches (1,5 µg/día), con un seguimiento de 4,8 años, y demostraron un aumento en el grosor de la piel del 7-15 % medido por ecografía. Por otra parte, Haapasaari et al 21 …”
Section: Hormonasunclassified
“…Skin biopsies were taken from the thigh thus eliminating confounding factors such as sun exposure and smoking (Maheux et al 1994). Other authors have also demonstrated increased skin thickness following HRT (Brincat et al 1985;Callens et al 1996;Sator et al 2001).…”
Section: Hormone Replacement Therapymentioning
confidence: 99%